Narrative Therapy as an Intervention for Post-Divorce Adjustment and Grief: Examining Psychological Outcomes - Batthyany , Karina; Kraus, Sabine; William , Erwin A; Yang, Yaliu (Journal of Psychosociological Research in Family and Culture, 2025)
Objective: This study aimed to evaluate the effectiveness of narrative therapy in improving post-divorce adjustment and reducing grief symptoms among individuals experiencing marital dissolution. Methods and Materials: A quasi-experimental design was used with a treatment group (n = 36) receiving ten structured narrative therapy sessions and a control group (n = 36) receiving no intervention. Participants were assessed at three time points: pre-test, post-test, and follow-up. Standardized measures, including the Post-Divorce Adjustment Scale (PDAS) and the Grief Experience Questionnaire (GEQ), were administered to evaluate changes over time. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests to determine within-group and between-group differences in post-divorce adjustment and grief levels. Findings: Results showed a significant improvement in post-divorce adjustment in the treatment group compared to the control group (F = 57.90, p = 0.0001). Grief levels significantly decreased in the treatment group over time (F = 71.92, p = 0.00001), with Bonferroni post-hoc comparisons indicating that post-divorce adjustment increased significantly from pre-test to post-test (p = 0.001) and was maintained at follow-up (p = 0.0003), while grief decreased significantly from pre-test to post-test (p = 0.0001) and continued to decline at follow-up (p = 0.00001). Conclusion: The findings suggest that narrative therapy is an effective intervention for enhancing post-divorce adjustment and reducing grief. By enabling individuals to reconstruct their divorce narratives, the therapy promotes emotional healing, resilience, and future-oriented self-perceptions. Narrative therapy should be considered a valuable therapeutic approach for individuals struggling with the emotional consequences of divorce.